DESPERATELY SEEKING UNITY: A POSTMODERN CRITIQUE - Wardah Al-Katiri (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2024)
In the direction of postmodern critique of modern nation-state characterized by, among others, homogeneity of culture and language, this article presents a case study of Indonesia which happened to be the world largest Muslim population. The nation-building process in a deeply pluralistic society of the Indonesian archipelago—of which forcing unity into diversity was a necessity—turned to be one of the greatest paradoxes. Namely: the very idea of unity for the pursuit pursuance of equity contradicts the premise of democracy, because forcing unity into diversity implies denouncing differences, and thus, a violation of human rights to be different. On that account, Indonesia’s struggle with diversity has falsified Huntington’s thesis, according to which cultural differences necessarily tend to lead to conflict. On the contrary, the plain reality of Indonesia demonstratesshows that the conflicts stemmed from nationalism and political-economic ideologies rather than cultural differences. Furthermore, through a reading of the Qur'an, I would like to bring into attention that the rights to be in different ‘traditions’ is associated with the rights to freedom of religion, and is a part and parcel of human dignity in Islam.